2020
DOI: 10.3390/plants9080967
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Transporters in Plant Cells: A Brief Review

Abstract: Amino acids are not only a nitrogen source that can be directly absorbed by plants, but also the major transport form of organic nitrogen in plants. A large number of amino acid transporters have been identified in different plant species. Despite belonging to different families, these amino acid transporters usually exhibit some general features, such as broad expression pattern and substrate selectivity. This review mainly focuses on transporters involved in amino acid uptake, phloem loading and unloading, x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 110 publications
(250 reference statements)
1
61
0
8
Order By: Relevance
“…Highly conserved histone chaperones are involved in nucleosome assembly, leading to remodelling of the chromatin structure during transcription or DNA replication [ 61 , 62 ]. Enrichment in the nucleosome assembly category was noted only in the non-primed plants of WL-S, which may indicate that chromatin organization is more advanced upon oxygen deprivation in WL-S than in WL-T. Functional prediction showed that target genes potentially regulated by lncRNAs in non-primed plants of WL-S were also specifically enriched in processes connected with transport inside the cells and between the plant organs in order to maintain homeostasis in the cells and to transport, among other things, a reduced form of nitrogen [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Highly conserved histone chaperones are involved in nucleosome assembly, leading to remodelling of the chromatin structure during transcription or DNA replication [ 61 , 62 ]. Enrichment in the nucleosome assembly category was noted only in the non-primed plants of WL-S, which may indicate that chromatin organization is more advanced upon oxygen deprivation in WL-S than in WL-T. Functional prediction showed that target genes potentially regulated by lncRNAs in non-primed plants of WL-S were also specifically enriched in processes connected with transport inside the cells and between the plant organs in order to maintain homeostasis in the cells and to transport, among other things, a reduced form of nitrogen [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…S7 and S8 ). The genes we chosen include MADS family genes that modulates nitrate translocation in rice [ 31 ]; WAKY family genes that influence rice phosphorus accumulation [ 32 ]; amino acid transporters ATL family genes [ 33 ]; PHYB family genes that responds to starvation [ 34 ]; ammonium transporter AMT family genes [ 35 ], and some genes relative to methylation and miRNA regulations [ 36 , 37 ]. Many research showed that gene methylation is highly correlated with transcription levels [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is a stereospeci c transporter and has wide speci city for neutral amino acids, such as alanine, asparagine and glutamine 54 . Its reported that amino acid transporters play crucial role in plant defense by controlling the transport of amino acid 54,55 . AAP4 was found to be upregulated in mango ginger rhizome when compared to ginger leaves and rhizome.…”
Section: Discussionmentioning
confidence: 99%